Clinical and Pathogenetic Parallels of Nonalcoholic Fatty Liver Disease and Gallstone Disease - Aleksey O. Bueverov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to analyze the data that has so far been accumulated on the pathogenetic association of gallstone disease (GD) and non-alcoholic fatty liver disease (NAFLD), as well as to assess the effect of cholecystectomy on the NAFLD course.Key findings. The relationship between GD and NAFLD is very complex and seems to be mutually aggravating. There is no doubt that there is an increased risk of GB in NAFLD patients, which is primarily associated with common pathogenetic mechanisms. These include central and peripheral insulin resistance, changes in the expression of transcription factors (liver X-receptor and farnesoid X-receptor) and the bile acid membrane receptors (TGR5). Conversely, the effect of GD on the NAFLD course is assumed, although the pathogenetic factors of this association are still unknown. In recent years, convincing data has emerged concerning the role of cholecystectomy in the NAFLD progression, which may be connected with the development of small intestinal bacterial overgrowth, as well as with the disruption of the endocrine balance and the signal function of bile acids.Conclusion. The connection between NAFLD, GD and cholecystectomy is complex and multifaceted. The study of this connection will allow new methods of treatment to be developed.